2017
DOI: 10.1016/j.heliyon.2017.e00360
|View full text |Cite
|
Sign up to set email alerts
|

The impact of finasteride and dutasteride treatments on proliferation, apoptosis, androgen receptor, 5α-reductase 1 and 5α-reductase 2 in TRAMP mouse prostates

Abstract: BackgroundPreviously, we studied the effect of finasteride- or dutasteride-containing diets in male C57BL/6 TRAMP x FVB mice. Pre (6 weeks of age) and post (12 weeks of age) groups received finasteride or dutasteride to determine the efficacy of these pharmaceuticals on prostate cancer (PCa) development in male C57BL/6 TRAMP x FVB mice. Post-Dutasteride treatment was more effective than Pre-Dutasteride treatment, and dutasteride treatments were more effective than finasteride treatments in decreasing prostatic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
1
1
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 51 publications
0
2
0
1
Order By: Relevance
“…Thus, it was concluded that the sharp decrease in androgen profile (testosterone and DHT) after gonadectomy led to significant reduction in prostate blood flow. In fact, prostatic hemodynamics is primarily regulated by androgen hormones [55][56][57][58][59][60]. Thus, the expected reduction in prostate blood supply after testicle removal is an indirect signal of treatment effectiveness [52].…”
Section: Plos Onementioning
confidence: 99%
“…Thus, it was concluded that the sharp decrease in androgen profile (testosterone and DHT) after gonadectomy led to significant reduction in prostate blood flow. In fact, prostatic hemodynamics is primarily regulated by androgen hormones [55][56][57][58][59][60]. Thus, the expected reduction in prostate blood supply after testicle removal is an indirect signal of treatment effectiveness [52].…”
Section: Plos Onementioning
confidence: 99%
“…These lower number of CAG repeats have been previously associated with elevated AR expression. This finding is of therapeutic interest, given the availability of 5-alphahydrogenase inhibitors which have been shown to decrease AR expression 83 . The 5-alphahydrogenase inhibitors have been reported to lower the incidence of prostate cancer and are an FDA-approved treatment for benign prostatic hyperplasia (BPH) 84 .…”
Section: Figure 8c Distribution Of Ages In Thementioning
confidence: 84%
“…Sabe-se que a utilização da finasterida em tratamentos contra o câncer de próstata, de modo a reduzir a atividade androgênica e, por conseguinte, a proliferação tumoral Opoku-Acheampong et al, 2017), pode levantar preocupações acerca de sua forma livre no ambiente e dos efeitos que tal inibidor pode ter sobre o desenvolvimento prostático. Os poucos estudos relacionados à exposição intrauterina à finasterida em machos demonstraram que tal exposição, que causa redução nos níveis de DHT ao longo do desenvolvimento prostático inicial, pode gerar redução no tamanho da próstata, problemas na formação dos alvéolos, diminuição da atividade secretória e, em dosagens mais altas, não formação dos lobos prostáticos.…”
Section: Discussionunclassified